1999
DOI: 10.1016/s1042-444x(99)00011-0
|View full text |Cite
|
Sign up to set email alerts
|

Stock market automation and the transmission of information between spot and futures markets

Abstract: The working paper series is for manuscripts in draft form. Comments are welcome and should be sent to the contact author. Please do not quote without permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Brailsford et al (1999) found that the automation of the stock market resulted in an increase of around 77% in contemporaneous public information transfer. With the entire bid-and-ask schedule and course of sales available on an almost real-time basis through e-trading directly to all market participants, investors do not have to rely on brokers for this information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Brailsford et al (1999) found that the automation of the stock market resulted in an increase of around 77% in contemporaneous public information transfer. With the entire bid-and-ask schedule and course of sales available on an almost real-time basis through e-trading directly to all market participants, investors do not have to rely on brokers for this information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Brailsford, T. J., Frino, A., Hodgson, A., and West, A., (1999), automation of equities trading has a three-fold effect on the market including: The transparency of the market with respect to price and trade information improves radically with participants being able view the entire bid and ask schedule and course of sales in real time; Reporting lags and errors reduced due to instantaneous dissemination of all market activity via electronic signals thereby producing a cleaner price feed for the market; and Faster trade execution is achieved for large portfolios of shares as parties to transactions no longer had to physically search each other out. Biais, Glosten and Spatt (2005), in their study noted that automation can lead liquidity to decrease because it does not allow the direct negotiation between traders for transactions and does not allow them to preserve a certain control on trading conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ates and Wang (2005) also study the regular futures contracts and E-mini futures contracts on the S&P 500 and NASDAQ 100 indices, and find that, after the learning period and when the electronic system achieves a sufficient level of liquidity, this market presents an increasing informational superiority, with information shares of 84.2-89.5% in the maturity period. Brailsford et al (1999) examine the impact of automated trading, introduced on September 1990 at the Australian stock market, on the information transmission between the stock and the futures market, and find that automated trading provides a richer and timelier information set which accelerates the price discovery process. Fung et al (2005) study the switching, on 6 June 2000, of the Hang Seng Index futures (Hong Kong) from floor trading to electronic trading, and show that the futures information share increases from 56% to 66%, while the futures common factor weight increases from 0.602 to 0.664.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Automation of capital markets has also been found to have instilled or enhanced transparency in market activities to an extent, with respect to price and trade information (Brailsford, Frino, Hodgson, & West, 1999;Grunbichler, Longstaff, & Schwartz, 1994;Hamilton, 1978;Jassawalla, 1989;Nabi, 2004;Picot, Bortenlaenger, Roehrl, 1995). Brailsford et al (1999) found that the automation of the stock market resulted in an increase of around 77% in contemporaneous public information transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Brailsford et al (1999) found that the automation of the stock market resulted in an increase of around 77% in contemporaneous public information transfer. With the entire bid-and-ask schedule and course of sales available on an almost real-time basis, and directly to all market participants, investors do not have to rely on brokers for this information.…”
Section: Introductionmentioning
confidence: 99%